2020
DOI: 10.1016/j.ijid.2020.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the presence of bacteria in low-volume preoperative aspirated synovial fluid by metagenomic next-generation sequencing

Abstract: Preoperative diagnosis is important for patients who need revision surgery due to PJI. Microbial culture plays an important role in PJI diagnosis, but the sensitivity of cultures is low when the sample amount is limited or when a patient is treated with antibiotics before sample collection. In this study, metagenomic next-generation sequencing (mNGS) was used to detect bacteria in preoperative puncture synovial fluid samples from patients with suspected PJI, and the preoperative and intraoperative culture resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Synovial polymerase chain reaction studies. Overall, 20 studies described the diagnostic accuracy of synovial fluid PCR in the detection of PJi, using the msis criteria as the standard reference test, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with baseline characteristics of individual studies shown in table i. three studies contributed to two data points each, as these studies published data on different PCR Fig. 6 Forest plot for synovial fluid calprotectin studies.…”
Section: Resultsmentioning
confidence: 99%
“…Synovial polymerase chain reaction studies. Overall, 20 studies described the diagnostic accuracy of synovial fluid PCR in the detection of PJi, using the msis criteria as the standard reference test, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with baseline characteristics of individual studies shown in table i. three studies contributed to two data points each, as these studies published data on different PCR Fig. 6 Forest plot for synovial fluid calprotectin studies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 158 ] Conventional diagnostic challenges in BJI due to the fastidious nature of the organisms, biofilm formation on implant surfaces, prior antibiotic administration, or limited sample availability, all contribute to the high rate of culture‐negative PJIs, the microbial etiology for which is challenging to diagnose. [ 159,160 ]…”
Section: Clinical Application Of Ngsmentioning
confidence: 99%
“…[ 162–164 ] mNGS should be highly recommended for the cases of culture‐negative BJI, limited sample volume obtained by joint cavity puncture, or when the patient has poor responses to empirical antibiotics therapy or debridement. [ 160,165 ]…”
Section: Clinical Application Of Ngsmentioning
confidence: 99%
“…However, literature relevant to clinical applications has mostly focused on its partial function of rapid detection in certain infectious diseases (e.g., central nervous system infections, respiratory infections, bone and joint infections, etc. ( Fang et al, 2020 ; Huang et al, 2020 ; Wilson et al, 2019 ; Yan et al, 2020 ; Zhang et al, 2020 )). On the other hand, to comprehensively interpret and evaluate the full-function of shotgun metagenomic sequencing (including pathogen identification and ARGs prediction) remains challenging, which needs more investigation and validation.…”
Section: Introductionmentioning
confidence: 99%